INFLUENCE OF DIGITAL REVIEWS ON CONSUMER FOOD CHOICES IN E-MARKETPLACES - Prima Welina Sinulingga; Effy Yuswita; Dina Novia Priminingtyas (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2025)
The rapid growth of e-commerce in Indonesia has positioned food, beverages, and groceries as the most frequently purchased product categories, accounting for 43.92% of online sales in 2023. Despite offering convenience, online food shopping carries inherent risks due to product perishability and the inability of consumers to directly assess product quality prior to payment. This study investigates the influence of online customer reviews and ratings on food purchasing decisions at Sayur Dapur Devita’s Shopee marketplace in Malang. Employing a quantitative approach, data were collected from 100 purposively selected respondents using the Cochran formula. Descriptive statistics and SEM-PLS analysis with SmartPLS 4.0 were applied. Findings reveal that most consumers are female, aged 13–28 years, students with bachelor/diploma degrees, earning IDR 1,000,000 – 2,000,000, and frequently purchasing vegetables and fruits. The analysis confirms that reviews and ratings significantly and positively affect purchasing decisions. Practical implications suggest encouraging consumer feedback, promptly responding to reviews, and diversifying product offerings.